2019
DOI: 10.1017/s0272263119000573
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Second Language Acquisition Between 1997 and 2018

Abstract: This study used the bibliometric method to examine the field of second language acquisition (SLA) between 1997 and 2018 to provide a systematic overview of the field and to discover major trends in SLA. Based on citation/cocitation information and keywords retrieved from Web of Science, this study performed three types of bibliometric analyses to identify the prominent scholarly documents, authors, research institutions, geographic regions, and research topics that have been highly influential in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 69 publications
(100 reference statements)
2
92
0
Order By: Relevance
“…Liu and O’Halloran, 2009) are leading multimodal analysts. As the analytical scope of applied linguistics extends from its traditional territory of language learning and teaching to professional and organizational communication, professional communication is gaining increasing popularity and impact, as evidenced in research by Bhatia (2010), Mondada (2014) and Zhang and Vásquez (2014). The discursive news values approach, conceived by Bednarek and Caple (2014, 2017), affords a new insight and analytical framework to study linguistic construction of news values, quickly drawing considerable scholarly attention in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Liu and O’Halloran, 2009) are leading multimodal analysts. As the analytical scope of applied linguistics extends from its traditional territory of language learning and teaching to professional and organizational communication, professional communication is gaining increasing popularity and impact, as evidenced in research by Bhatia (2010), Mondada (2014) and Zhang and Vásquez (2014). The discursive news values approach, conceived by Bednarek and Caple (2014, 2017), affords a new insight and analytical framework to study linguistic construction of news values, quickly drawing considerable scholarly attention in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang's (2019) recently published bibliometric analysis of second language acquisition (SLA) research provides yet another view of the field's sampling practices. This analysis shows clearly that the field is dominated heavily by Western scholarship.…”
Section: Sampling Practices In Applied Linguisticsmentioning
confidence: 99%
“…This analysis shows clearly that the field is dominated heavily by Western scholarship. Using the 16 most influential Applied Linguistics journals as determined by Al-Hoorie and Vitta (2018), Zhang (2019) analyzed the origins of the publications in these journals. The analysis showed that the field has been heavily dominated by journals published in the U.S., publications produced at prestigious North American research institutes, and scholars working in Anglo-Saxon environments (although Japanese scholarship has been strong, and Chinese scholarship is on the rise).…”
Section: Sampling Practices In Applied Linguisticsmentioning
confidence: 99%
“…Recent studies have further entrenched the case for vocabulary having a key role in L2 proficiency. For instance, a recent meta-analysis illustrated that vocabulary knowledge, in the aggregate, has a strong relationship with reading (r = .57) and listening (r = .56) proficiency (Zhang & Zhang, 2020). Structural equation modeling has likewise revealed that lexical measures (sophistication and cohesion) account for approximately 81% of Test of English as a Foreign Language (TOEFL) essay scores' variance, while syntactic measures are only indirectly involved (Kim & Crossley, 2018).…”
Section: L2 Instructed Vocabulary Acquisition Researchmentioning
confidence: 99%
“…Thus, we limited our focus to SSCI journals to increase the probability of reviewing the best‐quality research. Following Zhang (2020), who similarly focused upon SSCI journals, we make no judgments about non‐SSCI L2 journals and value their contributions to the field.…”
Section: Phase I: L2 Instructed Vocabulary Acquisition Research Effecmentioning
confidence: 99%